Honduras Economic DNA, June 2015 : Maintaining Commitment – With a Special Focus on Poverty and Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2015)
Successfully alleviating poverty, protecting social gains, and promoting shared prosperity in Honduras requires an ongoing commitment to sound macroeconomic and fiscal policies. The experience of the past decade has demonstrated that while accelerated growth is critical to increasing incomes among the poor, macroeconomic stability as well as improved fiscal space to adjust spending policies during downturns are equally vital to ensuring that these gains are sustained over time. In the past, substantial imbalances in the public accounts and high levels of debt have destabilized the Honduran economy, undermining wealth creation and perpetuating poverty. In the context of a slow and uncertain global recovery, reinforcing the countrys resilience to shocks will depend on the authorities’ commitment towards fiscal stabilization. The successful completion of the fiscal consolidation process will be a crucial first step to free up resources for targeted antipoverty programs. Honduras has been slow to recover from the global economic crisis, but recent developments present cause for optimism. After a negative growth of 1.4 percent in 2009, economic growth increased to an average of 3.8 percent during 2010-12, still below pre-crisis levels, before sliding to 2.8 percent in 2013. In 2014, growth improved to 3.1 percent and the outlook is expected to improve during 2015-2016, as the global economy continues to recover. Nevertheless, growth is expected to approach but not reach the rates observed in the mid-2000s.